IMPLEMENTASI INOVASI KEBIJAKAN PEMBELAJARAN JARAK JAUH PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) MASA PANDEMI COVID-19 DI SMA KOTA MATARAM - Ahsanul Khalik; Masnun Masnun; Ali Jadid (Jurusan P. IPS, FKIP, Universitas Mataram, 2022)
This study was motivated by the COVID-19 pandemic, which forced various lives to change so rapidly that the world of education had to adapt in the midst of chaos that threatens the safety of learning citizens. This situation encourages the Government to formulate learning policy innovations as an anchor for learning interaction modes, including in Islamic Religious Education (PAI) subjects which have specific characteristics compared to other subjects. On that basis, I saw the urgency to conduct research on learning innovations in PAI Education during the COVID-19 Pandemic in the City of Mataram. This study is a qualitative-descriptive field research. The data collected was analyzed using a grounded research paradigm where the data was extracted using several techniques such as observation, interviews, documentation, and Focus Group Discussion (FGD) techniques using purposive sampling technique. PJJ in its implementation is not as smooth as expected. The issues complained of are quite diverse. Starting from devices such as laptops and cellphones. Not all parents of students are able to facilitate their children with cellphones and laptops, especially since Corona, many parents have been laid off from their places of work, so that the family economy becomes more difficult. Inadequate internet network is also one of the obstacles in PJJ. PJJ conducted at home makes the discipline level of students decrease as many students are still late to enter the virtual learning room.